Ticket to Brussels. One-way or Return? Profiles and typology of Greek MEPs, 1981-2019 - Kakepaki, Manina; Karayiannis, Yiannis (The Greek Review of Social Research, 2021)
This article analyses the socio-demographic characteristics of all Greek MEPs elected to the European Parliament in the nine European elections from 1981 to 2019. We present new data on Greek MEPs and explore whether the demographic characteristics of those elected after 2014 (when the method of selecting candidates changed) and their social and political capital are different from the attributes of the previous Greek political class. We then move on to explore the relationship between the national and the European parliaments, questioning the extent to which the European Parliament functions as a starting point for political careers in the national arena, and whether it serves as a field for the emergence of a ‘supranational elite’, with distinct characteristics from those of the domestic elite, or whether it is a form of golden retirement for the domestic elite. Based on the available data, we propose a typology of Greek MEPs and analyze the specific characteristics of each type.